Therapeutic Potential of Clitoria ternatea Leaf Extract in reducing Parkinson’s Disease Symptoms in Drosophila - P, Beaulah Angel; R, Manjula K; NA, Shubha (Journal of Neonatal Surgery, 2025)
Phytochemicals, bioactive non-nutrient compounds found in plants, have been linked to reduced risks of chronic diseases, particularly those associated with oxidative stress. Parkinson’s disease (PD), a neurodegenerative disorder characterized by dopaminergic neuron loss and motor dysfunction, is influenced by oxidative stress and protein aggregation. In this study, we investigated the neuroprotective potential of Clitoria ternatea (CT) leaf extract in a Drosophila model of PD. The ethanolic extract of C. ternatea leaves was prepared using soxhlet extraction, and PD flies expressing human α-synuclein were generated through genetic crosses. Different concentrations (10, 50, and 100 μl/ml) of C. ternatea extract were administered to PD flies for 21 days, followed by behavioral assays to assess locomotion (climbing assay), seizure susceptibility (vortex assay), olfactory function (olfactory assay), and phototactic response (phototaxis assay). The results demonstrated that C. ternatea extract significantly improved locomotor function, reduced seizure recovery time, restored olfactory responses, and enhanced phototactic behavior in PD flies, with the highest improvement observed at 100 μl/ml concentration. These findings suggest that C. ternatea extract exerts neuroprotective effects, likely through its antioxidant and radical-scavenging properties, offering a potential therapeutic strategy for managing neurodegenerative disorders like Parkinson’s disease. Further studies are warranted to explore the underlying molecular mechanisms and its translational potential.